Before, During, and After the Covid-19 Pandemic (2018–2023), the Creditability of Stock Returns - Kristina Hasibuan; Elen Puspitasari (Universitas Negeri Semarang, 2025)
This research examines the relationship between stock returns and the financial performance of State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) before, during, and after the Covid-19 epidemic (2018–2019, 2020–2021, and 2022–2023). Financial performance indicators are the return on invested capital (ROIC), earnings per share (EPS), working capital turnover, total asset turnover, cash ratio, debt-to-equity Ratio, debt-to-asset Ratio, Current Ratio, and cash ratio. The study's primary sources are BUMN's annual financial reports and stock price data. A multiple linear regression model examined the connection between stock returns and financial performance. According to the findings, the variables influencing stock returns varied throughout time. Before the pandemic, cash ratio and earnings per share (EPS) significantly enhanced stock returns, reflecting investor attention to liquidity and profitability during economic stability. During the pandemic, total asset turnover emerged as the key variable impacting stock returns, emphasizing the necessity for efficient asset management amidst economic uncertainty. After the pandemic, earnings per share (EPS) and return on invested capital (ROIC) became the most influential factors, indicating investors' focus on profitability and the ability to generate investment returns. The study concludes that the COVID-19 epidemic has significantly impacted the correlation between stock returns and financial performance. These results provide corporate management and investors with important information for creating flexible financial plans that adjust to shifting market conditions.